Konseling Individu dengan Teknik Self Talk Untuk Menumbuhkan Self Acceptence pada Penyandang Disabilitas Fisik di Sentra Budi Perkasa Palembang - Masnia Natasya; Suryati Suryati; Muzaiyanah Muzaiyanah (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Individual Counseling Using Self Talk Techniques to Grow Self-Acceptance of Persons with Physical Disabilities at the Budi Perkasa Center Palembang". Self-acceptance is a positive attitude towards oneself, able and willing to accept one's own strengths and weaknesses, so that one can view the future more positively. The purpose of this study was to determine self-acceptance of persons with physical disabilities at the Budi Perkasa Center Palembang, and to find out the Individual Counseling Technique with Self Talk to foster Self Acceptance among persons with physical disabilities at the Budi Perkasa Center Palembang. This type of research is descriptive research with a qualitative approach, data collection tools interview, observation, and documentation. The subjects in this study were one social worker and two beneficiaries. The data analysis techniques used are: data reduction, data presentation and conclusion or verification. The results of this study indicate that self-acceptance in children with disabilities is able to accept themselves well without any rejection in themselves, are able to get along without shame and always think positively about their physical condition. Individual counseling using self-talk techniques to foster self-acceptance in persons with physical disabilities uses three stages, namely the initial stage, the middle stage and the final stage.